Technology in Banking : A Study of E-Banking Preferences of Service class in Jalandhar - Pahuja, Anurag; Kaur, Dalbir (Gyan Management Journal, 2007)
According to the purpose of this research, a review is provided of several comprehensive and revealing research studies citing the experiences of banks and customers with E-banking in India and abroad, which significantly predict the use and factors affecting usage of e-banking. Review indicates that there are almost negligible studies on the status of Internet banking in India though a number· of studies have been conducted abroad. (Balwinder and Pooja, 2006). fast life of today, which necessitates the need for one-stop outlets offering diverse financial products. They can hardly ignore tfie adoption of technology, which is playing a major role in increasing the efficiency, courtesy and speed of customer service provided by the banks. It is rightly said to be the age of E-banking. EBanking, a combination of the two words, Electronic technology and'13anking, is a process by which a customer performs banking transactions electronically without visiting a brick-and-mortar institution. It involves an extensive use of Information technology that eliminates the need for direct recourse to the bank by the customer
Keywords: E-Banking; comprehensive and revealing research; significantly